Using Landsat-7 satellite imagesin the determination of Surface Heat Islandin Damascus city (Damascus University Journal of arts and humanities sciences, 2022)
The phenomenon of Heat Islands(HI) appeared in most cities of the world, which experienced a great urban expansion. Researchers have distinguished several types of this phenomenon depending on the type of temperature measured. In this paper, we focus on studingthe type of surface heat islands (SHI) that depends on measuring surface temperature (LST) using satellite remote sensing data for Damascus City. Therefore, the Landsat-7 satellite images with a spatial resolution of 60 meters in the thermal field were used in the calculation of the surface temperature, after applying the necessary treatment processes of calibration and correction of the effect of the atmosphere and the effect of the emissivity of the surface. The results of the research emphasized the importance of using Landsat-7 thermal images with high spatial resolution to show the thermal footprint of Damascus and its urban impact on its countryside.The results of the spatial distribution of the surface temperature also showed the correlation of the formation of surface heat islands in the study area to urban uses with built areas (impervious surfaces) in the first place, followed by the areas of buildings within the city, and agricultural lands appeared as cold islands on the outskirts of the city. Paying attention to the planning aspects such as increasing green areas and the thoughtful selection of building materials used will have a clear impact in reducing the rise in surface temperature and thus the formation of surface heat islands.
Keywords: Surface Heat Island (SHI); Land Surface Temperature (LST); Landsat-7; Land use, Damascus